المطالع والمقاطع في شعر ابن الأبار القضاعي البلنسي - لقمان، شاكر (جامعة 8 ماي 1945 قالمة, 2015)
This study attempts, to follow sightings of poetry that was initiated by the poet Ibn El Abar's poems and indicate the diversity of the poems and how they are built, as the first thing that influences and attracts the hearer. And the nature of the verses as the last thing sticks in the reader's mind and to identify the extent of the impact.
تحاول هذه الدراسة، التي بين أيدينا أن تترصد المطالع الشعرية، التي استهل بها الشاعر ابن الأبار قصائده، وبيان تنوعها من قصيدة إلى أخرى وكيفية بنائها، باعتبارها أول ما يقرع سمع المتلقي ويجذب انتباهه، والوقوف على المقاطع، التي اختتم بها ابن الأبار قصائده، لمعرفة مدى مناسبتها لأغراضه الشعرية وتنوعها، وطبيعتها.
Keywords: الشعر العربي -- الإيقاعيات الصوتية -- البلنسي، ابن الأبار القضاعي، ت. 1260 م